Droplet dynamic behaviors on gas diffusion layer surface of various wettabilities in a PEMFC gas flow channel. Issue 13 (21st October 2021) - Wang, Yulin; Liu, Tao; Sun, Huan; Yao, Minchao; Liu, Shengchun; Qin, Yanzhou; Wang, Xiaodong
ABSTRACT: Droplet dynamic behaviors in a gas flow channel (GFC) of proton exchange membrane fuel cell (PEMFC) with gas diffusion layer (GDL) of various wettabilities are observed by using the volume of fluid (VOF) method in this work. Droplet deformation, detachment, breakup, and multiple droplets coalescence are investigated via an analysis of forces over the droplet. Results show that droplets tend to detach from a hydrophobic GDL surface at a high airflow velocity; while exhibiting significant deformation even breakup on a hydrophilic GDL surface. Besides, the interaction among the pressure force, shear force, wall adhesion force (arising from surface tension), and lift force over the droplet is examined to qualitatively elucidate the droplet dynamic behaviors. It is found that a hydrophobic GDL with a moderate airflow velocity can facilitate water removal from the GFC and maintain a relatively small spreading area; however, too high or too low an airflow velocity can cause a breakup or a slow drainage of the droplet, especially on a hydrophilic GDL surface. Thus, the design and operation of the PEMFC should consider both the wettability of GDL surface and the airflow velocity to achieve effective water management.